The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13052-021-01012-9
|View full text |Cite
|
Sign up to set email alerts
|

The neonatal assessment manual score (NAME) for improving the clinical management of infants: a perspective validity study

Abstract: Background and objectives The Neonatal Assessment Manual scorE (NAME) was developed to assist in the clinical management of infants in the neonatal ward by assessing their body’s compliance and homogeneity. The present study begins its validation process. Methods An expert panel of neonatal intensive care unit (NICU) professionals investigated the NAME face and content validity. Content validity was assessed through the content validity index (CVI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 43 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…In fact, the present study evaluated the interrater reliability and agreement of the NAME, as a part of the validation process of the NAME procedure. According to a previous study, the NAME seems to have both face and content validity; we also found some preliminary positive results for the NAME construct validity by assessing the relationships between age, weight, and the NAME (21). To strengthen the NAME validity, it is also necessary to evaluate whether there is a relationship between the NAME and the newborns' clinical conditions (for instance, the conditions reported in Table 2).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In fact, the present study evaluated the interrater reliability and agreement of the NAME, as a part of the validation process of the NAME procedure. According to a previous study, the NAME seems to have both face and content validity; we also found some preliminary positive results for the NAME construct validity by assessing the relationships between age, weight, and the NAME (21). To strengthen the NAME validity, it is also necessary to evaluate whether there is a relationship between the NAME and the newborns' clinical conditions (for instance, the conditions reported in Table 2).…”
Section: Discussionmentioning
confidence: 66%
“…Several studies demonstrated that procedures involving gentle touch, including light massage, osteopathic manipulative treatment, and kangaroo care, can induce positive effects in preterm babies: lower stress levels, better sleep quality, augmented heart rate and oxygen saturation regulation, improved growth, and higher survival likelihood (5,(7)(8)(9)(10)(11)(12)(13)(14)(15). However, since a procedure that uses touch purely as an assessment tool is lacking, we devised the NAME procedure: we described its rationale (9), started its validation process (21), and, in the present study, assessed its reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the age of children, there is now a wide international literature that underlines the importance of osteopathic intervention in the neonatal period, which highlights the effectiveness of osteopathic treatment in the presence of symptomatic and idiopathic asymmetries in the first months of life [37,38]. In this research, children have been involved from the age of 18 months, the age in which the first signs and symptoms of autism are usually observed, so intervening through osteopathic treatment in the first months of life means to be able to prevent the onset of dysfunctions (not related to autism) and their consequences; furthermore, this treatment could favor the development of other areas of functional regulation of the child, for example those related to sleep and feeding, reducing the tension and / or dysfunctional states already present, so continuing the prevention of further dysfunctions..…”
Section: Discussionmentioning
confidence: 99%